Efficient two-stage laser enrichment up to 99% of carbon-13 isotope by IR multiphoton dissociation of Freon molecules. (1st April 2022) - Laptev, V.B.; Pigul'skii, S.V.
Abstract: A new method for two-stage laser enrichment of carbon-13 ( 13 C) by isotope-selective IR multiphoton dissociation of Freon molecules is considered, which makes it possible to achieve a concentration of 13 C up to 99 % or higher with high productivity. At the first stage, as a result of the selective dissociation of CF2 HCl (Freon-22) molecules, it is expected to obtain a C2 F4 dissociation product enriched in 13 C up to 30 % – 50 %. At the second stage, CF2 Br2 (Freon-12B2) is proposed to be used as a working substance, which is synthesised from enriched C2 F4, and the enrichment process is carried out by selective deep 'burning-out' of the 12 C-containing component. Experiments on multiphoton dissociation of Freon-12B2 with an initial 13 CF2 Br2 concentration of 30 % in a mixture with oxygen by pulsed CO2 laser radiation are performed. It is shown that reaching a 13 CF2 Br2 concentration of no lower than 99 % is possible at high values of the elementary separation act parameters: 15 % – 18 % dissociation yield and 40 – 75 selectivity for 12 CF2 Br2 molecules.